The Effectiveness of Process-Oriented Guided Inquiry Learning to Improve Students’ Analytical Thinking Skills on Excretory System Topic - Rosadi, Ihwan; Maridi, Maridi; Sunarno, Widha (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Analytical thinking is a fundamental skill in education and which needs to be developed. This research would describe the effectiveness of process-oriented guided ınquiry learning (POGIL) to improve students’ analytical thinking skills on the topic of excretory system. This study used Research and Development (R&D) design. It was conducted on the 11th grade students of senior high school in Ngawi, East Java in 2017/2018 academic year with one group pre-test and post-test design. The data collection techniques used were validation, observation, and test. The data were analyzed descriptively, whereby the analysis result was tested with the Gain test. The result showed that the students’ analytical thinking skills was significantly increased as stated by the N-gain score. In control class, there were 2 students (6.7%) whose N-gain score was in the low category, 25 students (83.3%) whose N-gain score was in the medium category, and 3 students (10%) whose N-gain score was in the high category. In the experimental class, there were 21 students (70%) who got N-gain score in the medium category, and 9 students (30%) who got N-gain score in the high category. The results of this research showed that the students analytical thinking skills were different after the implementation of POGIL method. Therefore, it could be concluded that the POGIL was effective to improve students’ analytical thinking skills on the excretory system in senior high school. The information obtained from this research can be used as a tool to improve students’ analytical thinking skills.